Anopheles salivary biomarker as a proxy for estimating plasmodium falciparum malaria exposure on the Thailand-Myanmar border - Ya-Umphan, P; Cerqueira, D; Cottrell, G; Parker, D; Fowkes, F; Nosten, F; Corbel, V (American Society of Tropical Medicine and Hygiene, 2018)
Timely identification and treatment of malaria transmission “hot spots” is essential to achieve malaria elimination. Here we investigate the relevance of using an Anopheles salivary biomarker to estimate Plasmodium falciparum malaria exposure risk along the Thailand–Myanmar border to guide malaria control. Between May 2013 and December 2014, > 9,000 blood samples collected in a cluster randomized control trial were screened with serological assays to measure the antibody responses to Anopheles salivary antigen (gSG6-P1) and P. falciparum malaria antigens (circumsporozoite protein, merozoite surface protein 119 [MSP-119]). Plasmodium falciparum infections were monitored through passive and active case detection. Seroprevalence to gSG6-P1, MSP-119, and CSP were 71.8% (95% Confidence interval [CI]: 70.9, 72.7), 68.6% (95% CI: 67.7, 69.5), and 8.6% (95% CI: 8.0, 9.2), respectively. Multivariate analysis showed that individuals with the highest Ab response to gSG6-P1 had six times the odds of being positive to CSP antigens (P < 0.001) and two times the odds of P. falciparum infection compared with low gSG6-P1 responders (P = 0.004). Spatial scan statistics revealed the presence of clusters of gSG6-P1 that partially overlapped P. falciparum infections. The gSG6-P1 salivary biomarker represents a good proxy for estimating P. falciparum malaria risk and could serve to implement hot spot–targeted vector control interventions to achieve malaria elimination.